IL-33 regulates M1/M2 chemokine expression via mitochondrial redox-related mitophagy in human monocytes. (25th May 2022) - Lin, Yi-Ching; Lin, Yu-Chih; Tsai, Mei-Lan; Tsai, Yi-Giien; Kuo, Chao-Hung; Hung, Chih-Hsing
Abstract: Interleukin (IL)-33 is an epithelial-derived cytokine that enhances T helper (Th) 2 responses. Allergens and other agents induce IL-33 in asthma. Excessive production of reactive oxygen species (ROS) leads to airway inflammation. Mitophagy is the selective degradation of mitochondria by autophagy and often occurs in defective mitochondria, followed by ROS production. In the present study, we examined the effects of IL-33 on ROS production and mitophagy in human monocytes, and the detailed mechanisms were investigated. Human monocyte cell line THP-1 was pretreated with different concentrations of IL-33. ROS production was measured by flow cytometry. Mitochondrial involvement and the mitophagy and intercellular pathway activation were evaluated by quantitative real-time PCR, western blotting, and confocal microscopy, and cytokine/chemokine concentrations were detected by ELISA. The data showed that IL-33 alone could induce ROS expression in THP-1 cells. The expression of complex II and V mRNA was increased in the presence of IL-33. The mitophagy-related proteins PINK1, Parkin, and LC3 were regulated by IL-33 through the AMPK pathway. IL-33 significantly decreased M1-related cytokines CXCL-10 and TNF-α production and significantly increased M2-related cytokine CCL-22 production. In conclusion, IL-33 induces ROS production and subsequently influences mitophagy through AMPK activation, altering the macrophage-polarization phenotype of monocytes. Graphical abstract: Image 1 Highlights: IL-33 induces ROS production and mitochondrial complex II and V gene expression. IL-33 increases mitophagy-related protein expression via AMPK activation. IL-33-related mitophagy would promote M2-like effects in human monocytes. IL-33 influences redox-related mitophagy and subsequent chemokine expression in monocytes.